2011
DOI: 10.1097/brs.0b013e31822ef6de
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Correlation and Responsiveness of Patient-Reported Pain With Function and Quality-of-Life Outcomes After Spine Surgery

Abstract: Recommendation 1: When surgically treating CLBP, we recommend administering both a VAS for pain and a condition-specific physical measure such as the ODI before and after surgical intervention as these outcomes are the most treatment specific and responsive to change. Strength of recommendation: Strong.Recommendation 2: When evaluating the surgical outcomes for CLBP in the clinical-research setting, we recommend selecting a shorter version for measuring general HRQoL (e.g., SF-12, EQ-5D) to minimize clinician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 4 publications
2
128
0
Order By: Relevance
“…17,19,28,42 Clinical improvement for disability was defined using the concepts of MCID and SCB. MCID represents a critical threshold clinical change compared with the baseline that is considered to be meaningful (noticeable) improvement to the patient.…”
Section: Methodsmentioning
confidence: 99%
“…17,19,28,42 Clinical improvement for disability was defined using the concepts of MCID and SCB. MCID represents a critical threshold clinical change compared with the baseline that is considered to be meaningful (noticeable) improvement to the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Responsiveness of the EQ-5D was found to be moderate in a study in which exercise treatment was provided [6] and was sufficient for patients undergoing low-back surgery (area under the receiver operating characteristics [ROC] curve (AUC) of 0.77) [7]. One study reported the differences between pain, disability, and QOL after spinal surgery [8]. In general, responsiveness of the EQ-5D appeared higher in acute back care than in CLBP [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…41 This is also true for spine surgery. 23 In this study, we show that the SF-36 is a valid instrument to evaluate patients with IPSTs. Outcomes instruments are developed for specific test populations.…”
mentioning
confidence: 99%